Child's play: Addressing the young Cold War audience in Captain Video and His Video Rangers (1949–1955). - Baker, Djoymi (Critical Studies in Television, 2020)
This article argues the early science fiction television programme, Captain Video and His Video Rangers (DuMont, 1949–1955), addressed its young target audience directly as Cold War citizens, while encouraging them to undertake imaginative play in a form of early television fandom. The moral panic about the programme's perceived high levels of violence led to the negative portrayal of its young viewers in popular culture. Yet Captain Video 's modes of direct address reveal a concerted effort to constitute the early children's television audience around a playful intertextuality, bringing together consumerism, Cold War ideology and imaginative multi-genre engagement through child's play.